Aquatic habitat change within selected pools of the Upper Mississippi River from 1974-2000 - Asche, Derek (My University, 2007)
Impoundment of the Upper Mississippi River (UMR) in the 1930s created large areas of biologically diverse and productive backwater habitat. These areas may be threatened by rapid sediment accumulations that promote increased rates of allogenic succession. Aquatic habitat change in selected backwater areas trom Pool 4 to Pool 19 of the UMR was analyzed for a 25-year period (1975 to 2000) using color infrared aerial photography and geographic information system (GIS) software. The objective was to describe aquatic habitat changes and determine the extent to which these changes were consistent with allogenic succession. Four cover classes were recognized, representing a transition from open water to terrestrial vegetation. Several changes were observcd that were consistent with allogenic succession including a transition of emergent vegetation to grasses, forbs and/or woody vegetation. Other changes did not follow this trend including persistencc of open water/submersed vegetation and conversion of emergent vegetation to open water. The results suggest that allogenic succession does not adequately account for all aquatic habitat changes observed in this study. Other factors, including fetch and wave action, may account for persistence of open water conditions and loss of emergent vegetation.
Keywords: Aquatic habitats -- Mississippi River